PEMBERDAYAAN MASYARAKAT DALAM MEMANFAATKAN TANAMAN PAITAN (Thitonia diversifolia) SEBAGAI PAKAN DAN PUPUK ORGANIK DI BATAGAK KECAMATAN SUNGAI PUA KABUPATEN AGAM - Montesqrit Montesqrit; Yuliaty Shafan Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
Thitonia diversifolia are shrub plants that grow very fast and can reach up to 2 meters high. Theseplants are very much found in Nagari Batagak, Sungai Pua District, Agam Regency. The plant has notbeen used properly, which is usually cut down and then discarded. Not many people there use it as liquidor solid organic fertilizer or as animal feed ingredients. The purpose of this service is to empower thecommunity to utilize the local potential as organic feed and fertilizer. The method used is in the form ofcounseling and demonstration and application of the product. Counseling and demonstration carried outis the manufacture of solid and liquid organic fertilizers from linkages, utilization of linked plants as amixture of animal feed ingredients in the form of complete ration silage. The application carried out isthe application of the organic fertilizer to vegetable plants compared to chemical fertilizers and theapplication of complete ration silage to livestock. The application of solid and liquid organic fertilizersfrom paitan plants to vegetable mustard plants obtained morphological results (size, average weight,color, visualization, texture) and harvest age were not significantly different between organic vegetablesfertilized with organic fertilizers compared to fertilized organic vegetables with chemical fertilizers.Costs incurred for processing organic vegetables are cheaper than organic vegetables. The use of linkedplants as feed can be used up to 25% in complete ration silage.